Female Dangdut Singers and the Politics of Representation: A Critical Discourse Analysis - Nisak, Winda Khoirun (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2024)
This study examines how language constructs power and identity in the representation of women in dangdut music, focusing on song lyrics and stage performances. Using Critical Discourse Analysis (CDA), particularly Fairclough’s three-dimensional framework, the research investigates the linguistic and semiotic elements that shape the perception of female dangdut singers. Data were collected from popular dangdut songs and live performances, analyzing lexical choices, metaphors, and visual symbols. The findings reveal that Dangdut often portrays women through a dichotomy of empowerment and objectification. Lyrics frequently depict women as seductresses, reinforcing gender stereotypes, while performances emphasize bodily expressions that shape public perception. However, some modern interpretations challenge these narratives, offering alternative representations of female agency. This study highlights the intersection of language, ideology, and cultural discourse in Dangdut, emphasizing its role in shaping social norms and gender identity. The implications of this research contribute to discussions on gender representation in popular music and media discourse in Indonesia.